Synecdemus Novus: Presenting the Dataset of Human Activities on Crete (201–1204 C.E.) - Vera Klontza-Jaklova; Ricardo Fernandes; Adam Geisler; Manolis Klontzas (Journal of Open Archaeology Data, 2024)
Synecdemus Novus is a dataset of published archaeological sites, buildings, and associated markers located in Crete and dating between the Late Roman Period (3rd century C.E.) and the Venetian domination of the island (1204 C.E.). The dataset, consisting of 1234 entries, lists the location, spatial coordinates, type of the site/building/marker, chronological range, and relevant scholarly references for each entry. Synecdemus Novus is a resource for heritage management and allows researchers to investigate the spatio-temporal dynamics of settlement patterning in Crete between aforementioned periods.